Understanding Ciprofloxacin Failure in Pseudomonas aeruginosa Biofilm: Persister Cells Survive Matrix Disruption - Soares, Anaïs; Roussel, Valérie; Pestel-Caron, Martine; Barreau, Magalie; Caron, François; Bouffartigues, Emeline; Chevalier, Sylvie; Etienne, Manuel (Frontiers in Microbiology, 2019)
Biofilms are commonly recalcitrant to antibiotics, through incompletely elucidated mechanisms such as tolerance and persistence. We aimed at investigating how a P. aeruginosa biofilm escapes ciprofloxacin treatment. P. aeruginosa PA14 in vitro mature biofilms were challenged with supra-MIC ciprofloxacin concentrations. Cell viability was quantified by fluorescein diacetate assay. Population dynamics were determined by counts of surviving culturable cells. Biofilms were analysed using confocal laser scanning microscopy (CLSM), and the expression of genes involved in stringent response, toxin-antitoxin HigB/HigA, and type 3 secretion system (T3SS) was quantified by RT-qPCR in untreated and treated biofilms. Ciprofloxacin exposure resulted in an initial reduction of bacterial counts following a biphasic time-kill curve. After 24 h of treatment, the overall cell activity and the density of culturable cells significantly decreased as compared to untreated biofilm. No resistant mutant was isolated among the <1% surviving cells. Phenotypic adaptation towards persistence appeared to start after only 1 h of antibiotic exposure, by an overexpression of the genes involved in stringent response and in the toxin-antitoxin system, whereas the expression of genes encoding for the T3SS remained unchanged. After 4 h of ciprofloxacin exposure, stringent response genes returned to their basal level of expression. After a prolonged ciprofloxacin exposure, a deep alteration in the matrix structure that became thinner and lost mushroom-like aggregates was observed, in relation with reduced biovolumes of exopolysaccharides and extracellular DNA. These results support that ciprofloxacin might first induce the bacterial killing of most bacterial cells, but simultaneously activate stringent response mechanisms contributing to the switch of a subpopulation towards a persister phenotype. Once the persister phenotype is expressed, and despite an unexpected alteration of the biofilm matrix, ciprofloxacin fails to eradicate biofilm.